Ferocious Logics Unmaking the Algorithm - Munn, Luke (meson press, 2018)
Contemporary power manifests in the algorithmic. And yet this power seems incomprehensible: understood as code, it becomes apolitical; understood as a totality, it becomes overwhelming. This book takes an alternate approach, using it to unravel the operations of Uber and Palantir, Airbnb and Amazon Alexa. Moving off the whiteboard and into the world, the algorithmic must negotiate with frictions-the 'merely' technical routines of distributing data and running tasks coming together into broader social forces that shape subjectivities, steer bodies, and calibrate relationships. Driven by the imperatives of capital, the algorithmic exhausts subjects and spaces, a double move seeking to both exhaustively apprehend them and exhaust away their productivities. But these on-the-ground encounters also reveal that force is never guaranteed. The irreducibility of the world renders logic inadequate and control gives way to contingency.